Histone deacetylase 8 inhibition prevents the progression of peritoneal fibrosis by counteracting the epithelial-mesenchymal transition and blockade of M2 macrophage polarization - Zhou, Xun; Chen, Hui; Shi, Yingfeng; Li, Jinqing; Ma, Xiaoyan; Du, Lin; Hu, Yan; Tao, Min; Zhong, Qin; Yan, Danying; Zhuang, Shougang; Liu, Na (Frontiers in Immunology, 2023)
Background Peritoneal dialysis (PD) is an effective replacement therapy for end-stage renal disease patients. However, long-term exposure to peritoneal dialysate will lead to the development of peritoneal fibrosis. Epigenetics has been shown to play an important role in peritoneal fibrosis, but the role of histone deacetylases 8 (HDAC8) in peritoneal fibrosis have not been elucidated. In this research, we focused on the role and mechanisms of HDAC8 in peritoneal fibrosis and discussed the mechanisms involved. Methods We examined the expression of HDAC8 in the peritoneum and dialysis effluent of continuous PD patients. Then we assessed the role and mechanism of HDAC8 in peritoneal fibrosis progression in mouse model of peritoneal fibrosis induced by high glucose peritoneal dialysis fluid by using PCI-34051. In vitro, TGF-β1 or IL-4 were used to stimulate human peritoneal mesothelial cells (HPMCs) or RAW264.7 cells to establish two cell injury models to further explore the role and mechanism of HDAC8 in epithelial-mesenchymal transition (EMT) and macrophage polarization. Results We found that HDAC8 expressed highly in the peritoneum from patients with PD-related peritonitis. We further revealed that the level of HDAC8 in the dialysate increased over time, and HDAC8 was positively correlated with TGF-β1 and vascular endothelial growth factor (VEGF), and negatively correlated with cancer antigen 125. In mouse model of peritoneal fibrosis induced by high glucose dialysate, administration of PCI-34051 (a selective HDAC8 inhibitor) significantly prevented the progression of peritoneal fibrosis. Treatment with PCI-34051 blocked the phosphorylation of epidermal growth factor receptor (EGFR) and the activation of its downstream signaling pathways ERK1/2 and STAT3/HIF-1α. Inhibition of HDAC8 also reduced apoptosis. In vitro, HDAC8 silencing with PCI-34051 or siRNA inhibited TGF-β1-induced EMT and apoptosis in HPMCs. In addition, continuous high glucose dialysate or IL-4 stimulation induced M2 macrophage polarization. Blockade of HDAC8 reduced M2 macrophage polarization by inhibiting the activation of STAT6 and PI3K/Akt signaling pathways. Conclusions We demonstrated that HDAC8 promoted the EMT of HPMCs via EGFR/ERK1/2/STAT3/HIF-1α, induced M2 macrophage polarization via STAT6 and PI3K/Akt signaling pathways, and ultimately accelerated the process of peritoneal fibrosis.